2014
DOI: 10.1163/15685411-00002793
|View full text |Cite
|
Sign up to set email alerts
|

Consumption and prey size selection of the nematode Caenorhabditis elegans by different juvenile stages of freshwater fish

Abstract: Meiofauna, and nematodes in particular, play an essential role in the diet of certain juvenile freshwater fish. However, the specific consumption and prey size selection of fishes on nematodes is largely unrecognised. In this study, the effects of different juvenile stages of widely distributed common European freshwater fish, gudgeon (Gobio gobio), roach (Rutilus rutilus), ninespine stickleback (Pungitius pungitius), and two strains of common carp (Cyprinus carpio (scaled) and C. carpio (mirror)), on abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…In others, fish predation on meiofauna was assumed to be nearly negligible because these prey populations are large and, with their short generation times, are able to recover very quickly such that they are not strongly impacted by the comparatively small numbers of predatory fish (Coull, ; Shaw & Jenkins, ; Cross & Curran, ). Yet, in other studies, benthic meiofauna were shown to be an important food source, especially for small and juvenile fish species (Schückel et al ., ; Weber & Traunspurger, ,b). Although this discrepancy has been attributed to differences in methodologies (e.g.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In others, fish predation on meiofauna was assumed to be nearly negligible because these prey populations are large and, with their short generation times, are able to recover very quickly such that they are not strongly impacted by the comparatively small numbers of predatory fish (Coull, ; Shaw & Jenkins, ; Cross & Curran, ). Yet, in other studies, benthic meiofauna were shown to be an important food source, especially for small and juvenile fish species (Schückel et al ., ; Weber & Traunspurger, ,b). Although this discrepancy has been attributed to differences in methodologies (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…The main aim of this study was to close the knowledge gap between highly replicable small‐scale experiments and field studies with respect to the effects of fish predation on meiobenthic communities in natural freshwater ecosystems. At the same time, it is also important to recognise that the effect of fish predation on the meiobenthic community is often species specific (Dineen & Robertson, ; Spieth et al ., ; Weber & Traunspurger, ,b). For example, juvenile stages of the widely distributed carp Cyprinus carpio L. 1758 are bottom‐feeding consumers of meiofauna (Spieth et al ., ; Weber & Traunspurger, ,b).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…: Enclosures within tanks), the results indicated that meiobenthos may represent a significant, yet often overlooked, food resource for 0+ C. carpio. These findings were supported by another series of experiments involving different size classes of 0+ C. carpio of the fully-scaled and mirror phenotypes, which indicated both size-and strain-related differences in the rate of consumption of the nematode Caenorhabditis elegans (Weber and Traunspurger 2014a). As a result of a related aquarium-based experiment, in which however no effects on nitrogen, phosphorus and chlorophyll a were detected, a conclusion was made that 0+ C. carpio may be able to exert top-down control of meiobenthic communities (Weber and Traunspurger 2014b).…”
Section: Narrative Review Laboratory Experiments Aquariamentioning
confidence: 56%